Alterations in Sindbis Viral Envelope Proteins by Treating BHK cells with Glucosamine - Duda, Ernö (1975)
Addition of d-glucosamine to BHK cells infected with Sindbis virus inhibited the formation of the E-2 viral envelope from its precursor PE-2. Release of virus was blocked, and two new viral protein bands replaced the normal envelope protein bands detected in SDS-gel electropherograms of infected cell extracts.